An experimental assessment on low temperature combustion using diesel/biodiesel/C2, C5 alcohol blends in a diesel engine. (15th March 2021) - Ma, Qixin; Zhang, Quanchang; Zheng, Zunqing
Highlights: ITE increases with the addition of ethanol, but it has an opposite effect with the addition of pentanol at the same EGR. The Diesel-Biodiesel-Ethanol blends possess the best performance on soot emissions. The addition of higher alcohol has better performance on THC emissions than that of lower alcohol. Adopting lower alcohol ternary addition and medium EGR may be a better choice for diesel engines. Abstract: Alcohol additives in Diesel-Biodiesel (DB) blends were investigated on a modified single cylinder diesel engine with exhaust gas recirculation (EGR). The effects of lower and higher alcohol contents (10% ethanol, 20% ethanol and 10% pentanol by volume) with various EGR rates on combustion characteristics and emissions were evaluated. The results indicated that with the increase of EGR rates and increasing fraction of ethanol in DB blends, the ratio of premixed combustion will increase and the ignition delay (ID) will prolong, which lead to the increase of maximum pressure rise rate and peak value of heat release rate. Indicated thermal efficiency (ITE) increased firstly with EGR increasing and then decreased rapidly, but the EGR rates corresponding to the rapid decrease of ITE for the blends will be low compared to pure diesel. The Diesel-Biodiesel-Ethanol (DBE, the lower alcohol) blends showed the best performance on soot emissions among all the tested fuels even though there is no EGR. What's more, the DBE blends showed better nitrogen oxide (NOx) and carbon monoxide (CO) emissions at high EGR. However, the Diesel-Biodiesel-Pentanol (DBP, the higher alcohol) blends performed better THC emissions. Overall consideration, using diesel/biodiesel/ethanol ternary fuels under medium EGR rates may be a better choice for diesel engines.